PENGARUH JENIS KELAMIN DAN PENDIDIKAN TERHADAP FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS LASUSUA KABUPATEN KOLAKA UTARA TAHUN 2023 - Haddase, Hasriadi; ruf, Ma’; Zamli, Zamli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Tuberculosis is an infectious disease that can cause health problems and is also one of the top 10 causes of death from infectious diseases in the world, Pulmonary tuberculosis is caused by the bacterium Mycobacterium tuberculosis, which means that when people cough, they expel the bacteria into the air. The aim of the study was to determine the analysis of risk factors for pulmonary tuberculosis in the Work Area of the Lasusua Public Health Center, North Kolaka Regency 2023 years. This research was conducted in the working area of the Lasusua Public Health Center, North Kolaka Regency. The type of research used was an analytical survey with a